2023
DOI: 10.3390/s23020743
|View full text |Cite
|
Sign up to set email alerts
|

DMFL_Net: A Federated Learning-Based Framework for the Classification of COVID-19 from Multiple Chest Diseases Using X-rays

Abstract: Coronavirus Disease 2019 (COVID-19) is still a threat to global health and safety, and it is anticipated that deep learning (DL) will be the most effective way of detecting COVID-19 and other chest diseases such as lung cancer (LC), tuberculosis (TB), pneumothorax (PneuTh), and pneumonia (Pneu). However, data sharing across hospitals is hampered by patients’ right to privacy, leading to unexpected results from deep neural network (DNN) models. Federated learning (FL) is a game-changing concept since it allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…We have offered a comprehensive evaluation of the usefulness of the proposed structure, examining its performance both with and without the concentration key point elements being taken into consideration. The findings of the experiments reveal that the DCNN models work more effectively than the simple CNN model consistently [80]. The results of this study substantially indicate the effectiveness of the suggested method (ORB & VGG-19 with softmax) in classifying ten different chest diseases using CXR images.…”
Section: G Discussionmentioning
confidence: 52%
“…We have offered a comprehensive evaluation of the usefulness of the proposed structure, examining its performance both with and without the concentration key point elements being taken into consideration. The findings of the experiments reveal that the DCNN models work more effectively than the simple CNN model consistently [80]. The results of this study substantially indicate the effectiveness of the suggested method (ORB & VGG-19 with softmax) in classifying ten different chest diseases using CXR images.…”
Section: G Discussionmentioning
confidence: 52%
“…In order to assess the classification performance of the BFLPD framework for pandemic disease diagnosis in smart cities, we compared it against state-of-the-art models [24][25][26][27][28][29]. The results of this comparative analysis are presented in Table 2, showcasing the performance metrics obtained from the evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Deep neural networks [3, were a part of the pre-trained image classifier; however, the final convolutional layers of these networks resulted in a loss of the spatial resolution of the feature maps, which in turn restricted the classification capabilities of these models. In addition, the large number of neurons coupled to the input resulted in an insufficiently large filter size for these networks [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]73,74]. Because of this, the network could overlook significant traits as soon as they were discovered, which is a problem in how the network was designed.…”
Section: Discussionmentioning
confidence: 99%